Preliminary Archaeopetrological Study of the Lithic Industry from the l’Hort de la Boquera Rock Shelter (Margalef de Montsant, Tarragona, Spain) : Applying Mineralogical and Geochemical Techniques - Rey-Solé, Mar; García-Argüelles, Maria Pilar; Nadal, Jordi; Mangado, Xavier; Scherstén, Anders ; 0000-0002-2105-6172; Næraa, Tomas (Archaeologia Polona, 2018)
The l’Hort de la Boquera site is located in the northeastern part of Iberia and its stone tool assemblage includes up to 25,000 flint artefacts. This is the first approach to the analysis of the raw material through an archaeopetrological study. Results were obtained by use of mineralogical techniques: macroscopic and petrographic analysis, Scanning Electronic Microscopy (SEM), Micro-Raman and X-Ray diffraction (XRD); additionally, Laser Ablation Inductively Coupled Plasma Mass Spectrometry was applied. It has been possible to discriminate at least four flint categories, the ‘Evaporitic flint type’ (with two local subvarieties – ‘Common evaporitic’ and ‘Garnet’ varieties) that comes from local outcrops of the Ulldemolins Complex, and two flint types that had their origin further afield: the ‘Charophyta flint type’ (coming from the Torrente de Cinca Unit) and the ‘Dark flint type’ (from the La Serra Llarga Formation). These results make this study the most comprehensive analysis of raw materials that has been carried out in the area so far.
Publisher Copyright: © 2020 Towarzystwo Naukowe KUL. All rights reserved.
Keywords: Flint; Hort de la Boquera; KEY-WORDS: archeopetrology; Northeastern Iberia; Raw materials